Rancang Bangun Mesin Pengiris Pisang Otomatis: Rancang Bangun Mesin Pengiris Pisang Otomatis - Panjaitan, Jodi Palermo; Jaenudin, Jajang; Khamdi, Nur (Universitas Muhammadiyah Metro, 2023)
The process of slicing bananas in Pekanbaru in general still uses simple and manual tools, because the public does not really understand about the tool of making banana slicers and the level of efficiency of the tool is still lacking. The process of processed production of bananas in MSME businesses and home industries is still constrained by the limited resources used one of them in the process of slicing bananas as raw materials for banana chips. By using this Banana slicer machine will cut the time of slice and power in a long time that is still done manually. The goal of the author of this final task is to design a model of a mechanical banana slicer with two blades, comparing the production of a three-blade banana slicer with a four-blade slicer. The process of this machine starts from peeling bananas from the skin, bananas will be placed on the funnel that will go to the blade. The working system of banana slicer, Bananas will be avoided on the funnel, on the funnel there is a proximity sensor that will detect bananas that will serve to turn on the motor. After the motor lives the blade plate will rotate so that the banana is sliced then the banana will come out through the funnel out with the shape of the banana that has been sliced. Electronic system control is done sequentially more precisely in its application. From the test results obtained that the thickness of bananas amounted to 2.39 mm. The main drive on the slice is the 1 phasa motor and uses a dimmer to set the turn speed of the 1 phasa motor. The slice process travels at a speed of 450 rpm in 14,892 seconds. This machine can slice as many as 967 bananas in 1 hour.